2015
DOI: 10.1186/s13104-015-0983-5
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the role of alternative splicing within the RBM10v1 exon 10 tandem donor site

Abstract: BackgroundRBM10 is an RNA binding protein involved in the regulation of transcription, alternative splicing and message stabilization. Mutations in RBM10, which maps to the X chromosome, are associated with TARP syndrome, lung and pancreatic cancers. Two predominant isoforms of RBM10 exist, RBM10v1 and RBM10v2. Both variants have alternate isoforms that differ by one valine residue, at amino acid 354 (RBM10v1) or 277 (RBM10v2). It was recently observed that a novel point mutation at amino acid 354 of RBM10v1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 29 publications
1
15
1
Order By: Relevance
“…RBM10 was upregulated in lung adenocarcinoma cells and lung adenocarcinoma tissues, compared with normal lung cells and normal lung tissues adjacent to the tumor. Our findings are consistent with other findings (21,22,25,26). We also demonstrated that RBM10 was mainly expressed in the cell nucleus, and to the best of our knowledge, this is the first time this has been reported.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…RBM10 was upregulated in lung adenocarcinoma cells and lung adenocarcinoma tissues, compared with normal lung cells and normal lung tissues adjacent to the tumor. Our findings are consistent with other findings (21,22,25,26). We also demonstrated that RBM10 was mainly expressed in the cell nucleus, and to the best of our knowledge, this is the first time this has been reported.…”
Section: Discussionsupporting
confidence: 94%
“…At present, there are different opinions about whether RBM10 is a cancer-suppressor gene or an oncogene. In previous studies, opposing results have been found (22,26,38); however, the current study can partly explain the contradictory findings. RBM10 has three variants (RBM10v1, RBM10v2 and RBM10v3), with RBM10v1 and RBM10v2 playing the leading roles (11,23,39).…”
Section: Discussioncontrasting
confidence: 89%
“…The single valine residue that differentiates the two RBM10v1 variants, as well as the two RBM10v2 variants, occurs within the second RNA Recognition Motif (RRM) of RBM10. The presence or absence of this valine residue can influence the α-helical structure of this RRM domain, and could thus influence RBM10’s binding targets [ 13 , 14 ]. Although the functional implications of this modification have yet to be tested, the level of binding specificity exhibited by RBM5 suggests that (1) the presence or absence of this valine residue modifies RBM10’s structure sufficiently for proteins (at least RBM5) to be able to distinguish between variants, and (2) RBM10 splice variants have specific, potentially opposing, roles in the cell, and thus require specific regulation.…”
Section: Discussionmentioning
confidence: 99%
“…RBM10 has two main alternative splice variants termed RBM10 variant 1 ( RBM10v1 ) and RBM10 variant 2 ( RBM10v2 ) [ 10 12 ]. Each main RBM10 splice variant also codes for alternative isoforms with or without the addition of one valine residue ( Fig 1 ) [ 13 ]. Structurally, RBM10v2 and RBM5 share 53% homology at the amino acid level [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Functionally, overexpressed RBM10 causes apoptosis, and low levels of RBM10 are associated with decreased sensitivity to an apoptogenic stimulus [ 4 ], and increased colony formation [ 2 ]. Mechanistically, RBM10 is involved in mRNA stabilization [ 5 ] and regulation of alternative splicing [ 2 , 3 , 6 8 ].…”
Section: Introductionmentioning
confidence: 99%